ANALYSIS OF LEGAL PROTECTION FOR CHILDREN VICTIMS OF BULLYING BASED ON LAW NO. 35 OF 2014 CONCERNING CHILD PROTECTION: A CASE STUDY AT JAYA PANCUR BATU PRIVATE ELEMENTARY SCHOOL - Rio Apriyanto; Khairun Na'im; Elyani Elyani (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This study analyzes the legal protection of child victims of bullying based on Law No. 35 of 2014 concerning Child Protection, with a case study at Jaya Pancur Batu Private Elementary School. Data were collected through interviews, observations, and document studies, then analyzed in a qualitative descriptive manner. The results of the study showed that bullying in the school occurred in verbal, physical, and social forms. Although Law No. 35 of 2014 already exists, its implementation is still not optimal. Teachers and school staff do not fully understand the applicable legal provisions, and the anti-bullying policy at the school is not yet effective. In addition, psychological support for victims is minimal, and the involvement of law enforcement and child protection institutions is very limited. This study recommends increasing training for teachers, strengthening anti-bullying policies, providing better psychological services, and increasing the involvement of law enforcement and child protection agencies. In conclusion, the legal protection of children who are victims of bullying in schools needs to be strengthened through a more comprehensive and collaborative approach.